Implementasi Konsep Exposing the Locality pada Redesain Interior Showroom Furniture “Istana Rotan” di Semarang - Geena Giovanna Sunoto (Intra, 2016)
Rattan is one of Indonesia's wealth and has great potential in the furniture industry. Rattan furniture processed in many small villages, such as in Central Java, there are some villages which cultivate cane then distributed to big cities like Semarang. But in selling the products, rattans are still in a conventional manner that is selling goods on the street, making rattan image decreases. It is necessary for facilities to accommodate the rattan products. One of them is a showroom facility. In Semarang, there is a showroom that sells rattan products, namely “Istana Rotan”. But this showroom has many shortcomings. So that in this interior design, the designer want to redesign the “Istana Rotan” furniture showroom which is a facility that can accommodate rattan products and raise the image of rattan in Semarang. The redesign process is carried out from doing the survey, data exploration, making the concept, schematic, development, presentation drawings and working drawings, as well as the final results presentation as the model and material schemes. The concept raised is "exposing the locality furniture", where the application is more to the protrusion of the products shown. In addition, the use of local materials such as rattan, wood, brick combined with iron. Implementation of the concept of the design is done on a processing element of the interior showroom furniture “Istana Rotan”. In this scheme also introduced conveyor technology system in displaying rattan products.